(untitled) (Research in Agriculture Livestock and Fisheries, 2017)
Fifteen experimental trials were made in fifteen dogs in three different groups to study the degree of sedation produced by different premedicants, to evaluate and to compare their effects on various clinical parameters including different reflexes in dogs. These animals were premedicated with xylazine (1.1mg/kg), atropine (0.05mg/kg)-xylazine (1.1mg/kg) and diazepam (0.2mg/kg)-xylazine (1.1mg/kg) to observe their effect on different clinical and anaesthetic parameters. Diazepam-xylazine combination produced deep sedation while mild sedation was recorded with atropine-xylazine premedication. Respiration rate, heart rate and rectal temperature significantly decreased (P<0.05) in dogs of all three groups after fifteen minutes of premedication. Diazepam-xylazine produced marked reduction (P<0.05) on clinical parameters while atropine-xylazine produced mild to moderate reduction (P<0.05) on clinical parameters in dogs. All experimental dogs in different groups were anaesthetized with ketamine hydrochloride after fifteen minutes of premedication. The respiration rate, heart rate and rectal temperature reduced significantly (P<0.05) in xylazine-ketamine, atropinexylazine- ketamine and diazepam-xylazine-ketamine combination at 5, 10 and 15 min after induction when compared with pre-induction control values. The longest duration of anaesthesia (61.6 minutes) was obtained with diazepam-xylazine-ketamine combination while the shortest anaesthetic period (28.4 minutes) was observed in xylazine-ketamine combination. Diazepam-xylazine-ketamine combination produced longest recovery period (56.4 minutes) while the shortest recovery period (46.2 minutes) was observed with xylazineketamine combination. Atropine-xylazine-ketamine combination appears to be a safe combination for anaesthesia in dogs. Res. Agric. Livest. Fish.4(3): 209-214, December 2017